(untitled) (Bangladesh Journal of Nuclear Medicine, 2022)
Panniculitis indicates ‘inflammation of fat tissue’. Idiopathic Lobular Panniculitis is a rare condition in which inflammation occurs in the subcutaneous tissue, just beneath the skin. It is predominantly observed in women in the age group of 30-60 years. Occasionally, children may also be affected. We report a case of a 57 years old woman, who presented with multiple palpable skin lesions in both thigh, upper arms, breast and facial site specially left cheek and submandibular area. All of her laboratory findings including hematological and biochemical parameters were normal except slightly low white blood cell count. 18FDG PET-CT revealed multiple hypermetabolic lesions in the subcutaneous layer of skin and fat layers of the retroperitoneum. Diagnosis was confirmed by surgical biopsy which was reported as lobular panniculitis. Distinguishing true malignant cutaneous and subcutaneous benign might be difficult, but when lesions show high uptake of FDG, it can be related to an active inflammation. Extensive FDG uptake in a benign case like this is rare. Therefore, 18FDG PET-CT is not only helpful in detecting panniculitis but also feasible for identifying active state of the disease. Bangladesh J. Nuclear Med. 24(1&2): 57-59, 2021